PENGEMBANGAN SISTEM INFORMASI PENGIRIMAN BARANG PADA PT. KHARISMA SELARAS INDOTAMA MENGGUNAKAN METODE WATERFALL - Restu Ramadhan; Devi Yunita (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Digital information technology is currently developing rapidly and greatly affects information services for each organization, especially in freight shippingservices. Freight shipping is one of the activities of distributing goods and services that are often carried out by the people of Indonesia, both between regions and between islands. The convenience offered from technological developments in terms of processing information well, quickly and precisely. One of the information systems that is in great demand by the organization is the website. Websites are often called web, which are interpreted as a group of web pages that can be accessed globally and interrelated consisting of various kinds of text information, data, images, videos and sounds. PT. Kharisma Selaras Indotama is a company engaged in the shipping expedition services centered in Jakarta and has branches in Bekasi and Bandung that serve goods between goods from the nearest branches to between cities such as Aceh, Medan, Pekanbaru, and others using land, sea transportation , air. PT. Kharisma Selaras Indotama has deficiencies in information systems such as the absence of shipping status to the sender and manual admin in making reports. The purpose of this study is to create a website -based information system and MySQL database as a data storage medium using the Waterfall and Unified Modeling Language (UML) method to help customers in conducting delivery and admin in the report making process.